Remote Controlling and Monitoring of Induction Motors Through Internet - Abdülkadir Çakir; Hakan Çalis; Gökhan Turan (Institute of Advanced Engineering and Science, 2014)
Electric motors are workhorse of the industry. Induction motors are used more commonly than the other electric motors because of being low cost, robustness, and requiring less maintenance (especially squirrel-cage types), and able to work in harsh conditions. In this study, simultaneously remote powering of three separate single phase motors or one three-phase induction motor, when it is requested continuously remote data collection of motor currents, voltages, and remote monitoring of motor status are implemented. Moreover, preventing motors not running on low or high voltage conditions and allowing to run when the values return to nominal rates are provided. The design consists of PIC18F4620 microcontroller connected with ethernet board, sensor cards and control card. The developed software and HTML labels belonging to web interface are embedded in the microcontroller. The serial ethernet board contains HTML labels in its buffer memory. Thus, instead of using a separate host computer the serial ethernet board does the same hosting job. The remote powering of induction motors was done by the help of any device connecting to the internet with using an IP number assigned to the serial ethernet board. http://dx.doi.org/10.11591/telkomnika.v12i12.6719